Disaster Drills and Continuous Medical Education using Satellite-based Internet - Okada, Y.; Haruki, Y.; Ogushi, Y. (Methods of Information in Medicine, 2000)
We designed and evaluated a satellite-based Internet system for use in medical applications. Many experimental telemedicine projects use satellites, but we combined digital satellite communication with an ordinary telephone network to realize an economical countrywide network for emergency medicine and continuous medical education. The system appears to be a useful and practical technology for daily clinical activities.
Keywords: Telemedicine; Satellite; Multimedia; Emergency Medicine; Continuous Medical Education